1287Grief and mourning and its relation with anxiety and depressive symptoms during COVID-19 pandemic. (2nd September 2021) - Aguiar, Ana; Pinto, Marta; Duarte, Raquel
Abstract: Background: During these unprecedented times, individuals who experience the sudden death of a family member or friend, already miss the anticipatory grief and are now also prevented from a proper farewell. This study aimed to address prolonged grief disorder since the beginning of the COVID-19 pandemic Methods: A virtual snowball sampling survey was disseminated through social networking channels. The study enrolled participants from general resident population in Portugal with ≥18 years. Characteristics of the sample were summarized using descriptive statistics. Anxiety and depression symptoms are described by absolute and relative frequencies and compared through the Chi-square test. Results: A total of 929 participants completed the survey; 17.9% (n = 166) have lost someone since the beginning of the pandemic, making our final sample. Most were female (66.9%); median age of 35 years and 70.5% had a high education degree. Participants who had lost a grandparent consisted of 28.3% of the sample, father and/or mother 9.0%, and a friend 22.3%. We found a prevalence of 30.7% of anxiety symptoms and 10.2% of depression symptoms (p = 0.030). Also, 16.8% have had a high score on the PG13, which show that these people can mourned for longer periods. Conclusions: Paying the last tribute to a loved one is a mental health gesture that allows individuals to make amends and reconcile with life. Key messages: The need arises to give timely attention to the psychological consequences due to the COVID-19 pandemic concerning grief